Soaking up the Sun: Solar Energy Optimization during Pandemic, Study Case at Micro, Small and Medium Enterprises (MSME) Rattan Crafts Center in Trangsan Village, Sukoharjo, Central Java - Sujarwanto Dwiatmoko; Archibald Nagel; Jaka Windarta (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2022)
The National Energy General Plan has set a target of achieving the Renewable Energy mix by 23% by 2030, to achieve this the transition of energy to RE must be done immediately. Solar energy is one of the opportunities of renewable energy that is very abundant in Indonesia. Along with the issuance of the Minister of Energy and Mineral Resources Regulation number 49 of 2018 concerning the Use of Rooftop Solar Power System by Consumers of PT Perusahaan Listrik Negara (Persero) which provides opportunities for the utilization of PV Rooftop for household and commercial sector. In view of this, the Central Java Government plans to install Rooftop Power Plant in the Micro, Small and Medium Enterprises (MSME) Sector to develop the utilization of RE in the productive sector while improving the economic recovery of the Covid-19 pandemic. The use of renewable energy (EBT) is expected to save electricity costs in MSMEs. The results of planning using Helioscope software showed that in the three MSMEs with different PLTS capacities, namely 1 Kwp, 2.04 KWp and 4 KWp can produce annual energy production of 1,191 MWh, 2,433 MWh and 5,352 MWh respectively. After the installation of the PLTS, it was proven that in the first two months after installation energy consumption can decrease to minimum usage.